2013
DOI: 10.1152/ajpendo.00519.2012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic programming effects initiated in the suckling period predisposing for adult-onset obesity cannot be reversed by calorie restriction

Abstract: Srinivasan M, Mahmood S, Patel MS. Metabolic programming effects initiated in the suckling period predisposing for adult-onset obesity cannot be reversed by calorie restriction. Am J Physiol Endocrinol Metab 304: E486 -E494, 2013. First published December 18, 2012 doi:10.1152/ajpendo.00519.2012.-Neonatal rats reared on high-carbohydrate (HC) milk formula developed chronic hyperinsulinemia and adult-onset obesity due to programming of islets and the hypothalamic energy circuitry. In this study, calorie restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
2
16
0
1
Order By: Relevance
“…Decreased Stat3 and no change in Socs3 in mRNA levels were also observed in a previous study (31); however, no difference was observed in these two genes between NL and SL rats in the present study. Similar results on Lepr mRNA levels were observed in the HC, HC/PF, and HC/ PF/AL rats (37). Upon resumption of ad libitum feeding, reduction in Lepr mRNA expression was observed in SL/PF/AL rats, representing a negative correlation with the higher serum leptin levels and the SL phenotype in these rats.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Decreased Stat3 and no change in Socs3 in mRNA levels were also observed in a previous study (31); however, no difference was observed in these two genes between NL and SL rats in the present study. Similar results on Lepr mRNA levels were observed in the HC, HC/PF, and HC/ PF/AL rats (37). Upon resumption of ad libitum feeding, reduction in Lepr mRNA expression was observed in SL/PF/AL rats, representing a negative correlation with the higher serum leptin levels and the SL phenotype in these rats.…”
Section: Discussionsupporting
confidence: 82%
“…A similar observation was recently reported in an obese rat model in which metabolic programming was induced by feeding a milk formula high in carbohydrate-derived calories (HC) during the suckling period (37). Pair-feeding (mild CR) of SL rats from the time of weaning resulted in normalization of body weight, food intake, and serum hormonal levels in SL/PF rats, culminating in an NL-like metabolic phenotype in these rats.…”
Section: Discussionsupporting
confidence: 73%
“…Even in utero, the source of fetal hyperinsulinemia is endogenous: maternal glucose can cross the placenta, but maternal insulin cannot [116]. Importantly, central dysregulation of appetite induced in perinatal life by isocaloric high-carbohydrate formulas cannot be undone by subsequent periods of caloric restriction, even though whole-body metabolic status improves [772]. This dreadful pattern mimics the most common approaches for caloric restriction of obese humans, who quickly improve their metabolic status (Section 2.3) but often remain hungry (Section 7).…”
Section: Experimental Systems To Study the Atherometabolic Syndrome Amentioning
confidence: 99%
“…The stimulatory effect of the PNS is exerted via acetylcholine, whereas the inhibitory effect of the SNS is exerted via norepinephrine. In vivo and in vitro studies on the insulin secretory capacity of islets from HC rats indicated an augmented response to cholinergic stimulation and a reduced sensitivity to adrenergic inhibition, suggesting that an altered ANS regulation contributes to the hypersecretory capacity of the HC islet cells [82].…”
Section: Overnutrition By Early Overfeedmentioning
confidence: 96%
“…High carbohydrate milk formula until the time of weaning resulted in chronic hyperinsulinemia and adult-onset obesity (HC phenotype) in these rats supported by hypersecretory capacity of HC islets and hypothalamic alterations predisposing to hyperphagia [82]. Insulin secretion by pancreatic islets is under the control of peripheral (circulating blood glucose concentrations) and central Autonomic Nervous System (ANS) mechanisms.…”
Section: Overnutrition By Early Overfeedmentioning
confidence: 99%